2004
DOI: 10.1038/sj.ejhg.5201320
|View full text |Cite
|
Sign up to set email alerts
|

Phenylbutyrate increases SMN gene expression in spinal muscular atrophy patients

Abstract: Spinal muscular atrophy (SMA) is caused by insufficient levels of survival motor neuron (SMN) protein.Recently, we found that sodium 4-phenylbutyrate (PB), a well-tolerated FDA approved drug, enhances SMN gene expression in vitro. We provide here the first evidence that oral administration of PB (triButyrate s ) significantly increases SMN expression in leukocytes of SMA patients. This finding provides a strong rationale to further investigate the effects of PB as also supported by preliminary clinical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(88 citation statements)
references
References 11 publications
2
84
1
1
Order By: Relevance
“…Some therapeutic approaches aim to increase the amount of SMN protein produced by SMN2 through promoter activation, reduction of exon 7 alternative splicing, or both. [13][14][15][16][17][18][19][20][21][22] Some of these approaches are being investigated in ongoing or planned clinical trials, and great efforts have been done to identify the most appropriate clinical outcome measures for patients affected from various severities. 23 In this view, it would be very useful to have reliable biomarkers of disease severity and response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Some therapeutic approaches aim to increase the amount of SMN protein produced by SMN2 through promoter activation, reduction of exon 7 alternative splicing, or both. [13][14][15][16][17][18][19][20][21][22] Some of these approaches are being investigated in ongoing or planned clinical trials, and great efforts have been done to identify the most appropriate clinical outcome measures for patients affected from various severities. 23 In this view, it would be very useful to have reliable biomarkers of disease severity and response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Similar studies with hydroxyurea (HU) in EBV-immortalized SMA lymphoblasts 18 have shown an increase in the FL-SMN/D7-SMN (FL/D7 ratio). Pilot trials with these drugs have been performed in SMA patients and results were promising, [19][20][21] leading to the development of placebo-controlled clinical trials. PBA has been investigated in a double-blind placebocontrolled trial in 107 children with type II SMA.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations into the pathogenesis of spinal muscular atrophy (SMA) have led to hope that a specific therapy might soon be possible [1,2]. This prospect raises important concerns about the best manner for testing a putative therapy [3].…”
Section: Introductionmentioning
confidence: 99%